Factors affecting Brand Loyalty on Imported Instant Noodles Products mediated by Brand Trust - Andreas Yoshiro Ogawa; Fendy Cuandra (Jurnal Bisnis dan Akuntansi, 2022)
Imported products that are often favored are instant noodles, there is also an urge to immediately try and buy these products in line with current trends. The research was carried out with the aim of knowing brand loyalty in imported instant noodle products with brand trust as a mediation which was influenced by the variables of brand experience, perceived value, brand association, and brand awareness. The sample of this research is the Millennial/Y/Z generation in Batam City, with a sample of 408 data. Furthermore, the processing of this sample data will utilize the SmartPLS 3.2.9 software. The finding of this study showed that brand loyalty has direct effect by brand experience, perceived value, and brand trust, while brand association and brand awareness were not. The direct test also shows that brand trust is positively and significantly influenced by perceived value, brand association, and brand trust, while brand experience is not. The indirect test results through brand trust only succeeded in mediating brand awareness on brand loyalty, while other variables did not.